1992
DOI: 10.1128/aac.36.4.757
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of S-1108, a new oral cephem antibiotic, and metabolic profiles of its metabolites in humans

Abstract: The metabolism and pharmacokinetics of pivalic acid, a major metabolite of S-1108, were studied with three healthy volunteers. Concentrations of S-1006 (the active compound), pivalic acid, and pivaloylcarnitine in plasma and urine were measured after administration of S-1108. Recoveries in urine at the doses of S-1108 given (100 and 200 mg) were 33 to 41% for S-1006, 93% for total pivalic acid, and 89 to 94% for pivaloylcarnitine in 24 h, and maximum concentrations in plasma were 2 ,ug of S-1006 per ml, 1 ,ug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 16 publications
(25 reference statements)
0
29
1
Order By: Relevance
“…This increase of Tol-Car is in accordance with the reported induction of carnitine acyl transferases (Katsutani et al, 2000) and increases in free carnitine and CoA levels after pretreatment with fibrates (Gregus et al, 1998). Acyl carnitine esters are rarely observed metabolites of xenobiotic carboxylic acids, and to our knowledge, the only xenobiotic carnitine esters that have been previously identified in vivo are the pivaloyl (Vickers et al, 1985;Totsuka et al, 1992), valproyl (Melegh et al, 1990), and zomepirac carnitine esters (Olsen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This increase of Tol-Car is in accordance with the reported induction of carnitine acyl transferases (Katsutani et al, 2000) and increases in free carnitine and CoA levels after pretreatment with fibrates (Gregus et al, 1998). Acyl carnitine esters are rarely observed metabolites of xenobiotic carboxylic acids, and to our knowledge, the only xenobiotic carnitine esters that have been previously identified in vivo are the pivaloyl (Vickers et al, 1985;Totsuka et al, 1992), valproyl (Melegh et al, 1990), and zomepirac carnitine esters (Olsen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is suggested that a side effect such as muscle disorders may be unlikely in humans because the pivalic acid left from S-1108 is almost quantitatively conjugated with carnitine in the human body and is excreted rapidly into the urine (21,28). The safety of the clinical use of S-1108 given at 200 mg three times a day has been established in phase I clinical studies (21,27).…”
mentioning
confidence: 99%
“…Free pivalic acid accounted for most of the radioactivity in plasma following the administration of [pivaloyl- 14 C]S-1108 in both rats and rabbits. There is a great difference in the metabolic profile of pivalic acid between animals and humans; free pivalic acid was hardly found in human plasma (28).…”
mentioning
confidence: 99%
“…It was reported that the generated formaldehyde was rapidly metabolized and the produced carbon dioxide was excreted via expiration, as in the pivoxil series. [29][30][31][32] The hydrolysates were analyzed by HPLC, as shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%